Enhancing Academic Knowledge Dissemination: A Comprehensive Guide to Crafting Survey, Review, and Systematic Literature Review Articles - Younis, Hussain A.; Hayder, Israa M.; Salisu, Sani; Muthmainnah, Muthmainnah; Shahid, Misbah; Younis, Hameed Abdulkareem (Yayasan Corolla Education Centre, 2024)
This article provides a comprehensive and concise guide to the distinct steps involved in writing survey articles, review articles, and systematic literature review articles. These three types of articles play pivotal roles in summarizing, analyzing, and synthesizing existing research, thereby contributing to the dissemination of knowledge in various academic fields. For survey articles, the key steps encompass topic selection, extensive literature review, logical organization, and critical analysis. In contrast, review articles focus on selecting, summarizing, and evaluating pertinent research, while providing context and addressing controversies. Systematic literature review articles demand a methodical approach, beginning with a well-defined research question, protocol development, comprehensive literature search, stringent inclusion criteria, data extraction, quality assessment, data synthesis, and transparent reporting. This guide aims to assist researchers, scholars, and students in navigating the intricate process of producing high-quality articles in these genres, facilitating knowledge dissemination, and contributing to academic advancement. By elucidating the unique requirements and methodologies associated with each type of article, this comprehensive guide empowers writers to effectively communicate existing knowledge and enhance scholarly conversation in their respective fields.